Kajian Sastra Bandingan Pada Lirik Lagu Demi Kowe Karya Pendhoza dan Merantau Karya Abah Lala - Achsani, Ferdian (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This study aims to reveal the similarities and differences in Pendhoza's Demi Kowe song lyrics with the song lyrics Merantau by Abah Lala. This research is included in the type of qualitative descriptive research with a comparative literary approach. The data collection technique used is the technique of reading and recording. The researcher reads the two song lyrics and records the similarities and differences between the two song lyrics. Data analysis techniques use interactive techniques that include data reduction processes, data display and conclusion drawing. The results showed that the two songs had similarities and differences. The similarity between the two songs lies in the character values, please help, discipline, responsibility, and independence. The difference between the two songs can be seen in terms of the story that Demi Kowe's song lyrics tell more about the return of a man after going overseas to keep his promises. In Demi Kowe's song lyrics, religious values were also found that were not found in Merantau's song lyrics. In the song lyrics of Merantau the difference lies in the content of the story that tells about the struggle of a husband who lives in the land of rantau. In addition, in the song lyrics Merantau also tells about the suspicions and emotions of a husband towards the wife who was left at home.